Biliary peritonitis caused by a leaking T-tube fistula disconnected at the point of contact with the anterior abdominal wall: a case report. - Nikolić, Marko; Karthikesalingam, Alan; Nachimuthu, Senthil; Tang, Tjun Y; Harris, Adrian M (Springer Science and Business Media LLC, 2008)
INTRODUCTION: Operations on the common bile duct may lead to potentially serious complications such as biliary peritonitis. T-tube insertion is performed to reduce the risk of this occurring postoperatively. Biliary leakage at the point of insertion into the common bile duct, or along the fistula, can sometimes occur after T-tube removal and this has been reported extensively in the literature. We report a case where the site at which the T-tube fistula leaked proved to be the point of contact between the fistula and the anterior abdominal wall, a previously unreported complication. CASE PRESENTATION: A 36-year-old sub-Saharan African woman presented with gallstone-induced pancreatitis and, once her symptoms settled, laparoscopic cholecystectomy was performed, common bile duct stones were removed and a T-tube was inserted. Three weeks later, T-tube removal led to biliary peritonitis due to the disconnection of the T-tube fistula which was recannulated laparoscopically using a Latex drain. CONCLUSION: This case highlights a previously unreported mechanism for bile leak following T-tube removal caused by detachment of a fistula tract at its contact point with the anterior abdominal wall. Hepatobiliary surgeons should be aware of this mechanism of biliary leakage and the use of laparoscopy to recannulate the fistula.
Keywords: 1103 Clinical Sciences; Digestive Diseases; Liver Disease; Rare Diseases; Oral and Gastrointestinal